2011
DOI: 10.1186/1471-2121-12-56
|View full text |Cite
|
Sign up to set email alerts
|

Unfertilized frog eggs die by apoptosis following meiotic exit

Abstract: BackgroundA characteristic feature of frog reproduction is external fertilization accomplished outside the female's body. Mature fertilization-competent frog eggs are arrested at the meiotic metaphase II with high activity of the key meiotic regulators, maturation promoting factor (MPF) and cytostatic factor (CSF), awaiting fertilization. If the eggs are not fertilized within several hours of ovulation, they deteriorate and ultimately die by as yet unknown mechanism.ResultsHere, we report that the vast majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(77 citation statements)
references
References 37 publications
8
61
1
Order By: Relevance
“…Apoptosis-related and regulatory genes showed much higher expression variations. High expression variation of apoptosis-related genes, such as bid, bak, mcl1, casp3, casp7 , may help to explain a substantial heterogeneity of apoptotic response observed in unfertilized Xenopus eggs 9 . These results strongly suggested that monitoring transcript levels in single oocytes and eggs rather than in cell populations should be used for quantitative transcript profiling in these cells to circumvent intrinsically large gene expression heterogeneity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Apoptosis-related and regulatory genes showed much higher expression variations. High expression variation of apoptosis-related genes, such as bid, bak, mcl1, casp3, casp7 , may help to explain a substantial heterogeneity of apoptotic response observed in unfertilized Xenopus eggs 9 . These results strongly suggested that monitoring transcript levels in single oocytes and eggs rather than in cell populations should be used for quantitative transcript profiling in these cells to circumvent intrinsically large gene expression heterogeneity.…”
Section: Resultsmentioning
confidence: 98%
“…They can be collected freshly from living frogs and treated after isolation like a primary cell culture. Recently, aging unfertilized Xenopus eggs were found to die by a classical apoptotic process after the spontaneous exit from meiotic arrest 9-11 . In the present study, to bypass large cell-to-cell variation of the transcript levels in the oocyte/egg population, single-cell gene expression analysis was implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, two research groups, including ours, reported that the unfertilized Xenopus eggs laid outside of the frog body die by a well-defined apoptotic process [20,21]. In this case too, meiotic exit was found to precede apoptosis [21].…”
Section: Introductionmentioning
confidence: 96%
“…The size also allows injections to alter ionic composition or regulate the activity of different proteins (Dascal, 1987). Previous studies have shown that the X. laevis oocyte displays a normal apoptotic process, which includes activation of caspases, cytochrome c release from the mitochondria, nuclear condensation and ATP depletion (Braun et al, 2003;Johnson et al, 2010;Nutt et al, 2005;Tokmakov et al, 2011). The expression level of endogenous channels is low (Dascal, 1987) and this makes them suitable to explore the importance of ion channels and intracellular ion concentrations in the apoptotic process.…”
Section: 3mentioning
confidence: 99%
“…laevis oocytes display a normal apoptotic process compared to other cells including cytochrome c release and activation of caspase-3 (Braun et al, 2003;Johnson et al, 2010;Nutt et al, 2005;Tokmakov et al, 2011). In papers I-III, caspase-3 activity was measured by the fluorescence of 7-amino-4-methylcoumarin (AMC) resulting from the cleavage of acetyl Asp-Glu-Val-Asp 7-amido-4-methylcoumarin (Ac-DEVD-AMC) by activated caspase-3.…”
Section: Induction and Detection Of Apoptosismentioning
confidence: 99%